Transinsularidade perante a natureza. Educação ambiental através da banda desenhada Aguinha!! De Cabo Verde às Canárias... e vice-versa - Jankowski, Jakub (Studia Romanica Posnaniensia, 2023)
This paper proposes a contextualization of the didactic comic book Aguinha!! De Cabo Verde às Canárias... e vice-versa. The comic book in question emerged as part of the institutional project financed by European funds, but at the plot level it hides any explicit affinities with Europe. For this reason, we chose to analyze the contents of the book in the transinsular order and to draw both on the concept of environmental education and on border thinking. It is also proposed to frame this comic book as a complementary, non-autonomous didactic material.